1976
DOI: 10.1177/030098587601300506
|View full text |Cite
|
Sign up to set email alerts
|

Canine Leishmaniasis with Amyloidosis

Abstract: Abstract. Visceral leishmaniasis was diagnosed in a 2-year-old male Great Dane imported from Greece. The clinical signs included anemia, diarrhea, weight loss, proteinuria, and hyperglobulinemia with increases in a*-and y-regions. At necropsy there was plasmalymphocytic and macrophage infiltration of spleen, macrophage infiltration of bone marrow, intracellular organisms of macrophages having the ultrastructural characteristics of Leishmania species, and severe amyloidosis of the spleen, liver, and kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
3
15
0
Order By: Relevance
“…In both canine and hamster experimental infections, the renal abnor malities described are the results of short-term experi ments, in a selected canine breed or in golden hamsters, with selected species of visceral Leishmania, such as the Khartum strain and L.chagasior L.donovani 1, S, respec tively [17,18], The results of these studies revealed monomorphic renal lesions which were quite different from those found in human and canine natural leishmaniasis. In fact, in both experimental conditions, after the devel opment of mesangial proliferative GN, cellular prolifera tion was replaced in a very short time by the deposition of amyloid material, a finding which seems to be sporadic in the natural series [8,9,19]. In our study, amyloid deposits were a sporadic observation outlining the importance of specific factors related with the host immune response associated with the synthesis and deposition of amyloid.…”
Section: Discussionsupporting
confidence: 52%
“…In both canine and hamster experimental infections, the renal abnor malities described are the results of short-term experi ments, in a selected canine breed or in golden hamsters, with selected species of visceral Leishmania, such as the Khartum strain and L.chagasior L.donovani 1, S, respec tively [17,18], The results of these studies revealed monomorphic renal lesions which were quite different from those found in human and canine natural leishmaniasis. In fact, in both experimental conditions, after the devel opment of mesangial proliferative GN, cellular prolifera tion was replaced in a very short time by the deposition of amyloid material, a finding which seems to be sporadic in the natural series [8,9,19]. In our study, amyloid deposits were a sporadic observation outlining the importance of specific factors related with the host immune response associated with the synthesis and deposition of amyloid.…”
Section: Discussionsupporting
confidence: 52%
“…However, we believe that this ‘biological fact’ does not jeopardize the interpretation of the parasitological analysis since this protocol has already been validated . This lower renal parasite tissue is in concordance with the literature for naturally infected dogs and experimentally infected dogs …”
Section: Discussionsupporting
confidence: 88%
“…These authors proposed the dog as a model that reproduces HVL describing classical lesions in livers, spleens and lymph nodes, but not describing renal pathology. Other studies with experimentally infected dogs did not mention or explore the renal anatomical pathology …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 45% of systemic amyloidosis reported in the literature is AA amyloidosis. Amyloidosis has been described in spleen and liver of dogs naturally infected with L. infantum (Bely and Apathy, 2000;Poli et al, 1991;George et al, 1976). In hamsters, this pathology has been reported in adrenal gland (Novoa et al, 1990) in mice amyloidosis is most common in liver (Figure 1), spleen and kidney (Figure 2) Here, inflammatory infiltrates were observed in both medullary and cortical regions, however amyloidosis depositions were not demonstrated, suggesting passage of parasitic antigen though these organs but without evidence of parasites.…”
Section: Amyloidosis X Leishmaniasismentioning
confidence: 99%